Freud's Mass Hypnosis with Spinoza's Superstitious Wonder: Balibar's Multiple Transindividuality. Issue 1 (2nd January 2018) - Davidson, Christopher
Abstract: This response focuses on Balibar's method of thinking transindividuality through multiple figures, in their similarities as well as their productive differences. His essay 'Philosophies of the Transindividual: Spinoza, Marx, Freud' combines the three titular figures in order to better think the multifaceted idea of 'classical' transindividuality. Balibar's method combines the three but nonetheless maintains their dissimilarities as real differences. This response attempts to test or apply that method in two ways. The first application links Balibar's analysis of Freud's hypnotic leader with a theme Balibar does not here discuss: wonder's connection to superstition in Spinoza. At the level of their effects, superstitious wonder and hypnosis are nearly identical transindividual processes which lead to affective mass formation. However, their causes are quite distinct. This response details the similar effects and different causes, then asks the question: does their difference render them irreconcilable or complementary? Given the prominent role Spinoza plays in Balibar's work, and the strong overall equivalence of wonder and hypnosis, this first application of Balibar's method of multiple combination likely presents a complementarity rather than a conflict. This response's second application, attempting to integrate another figure into the transindividual multiple, presents greater difficulties: what role, if any, could Foucault play in Balibar's transindividuality? With Foucault, the tensions or differences perhaps amount to fundamental and thoroughgoing incompatibilities. However, combining Foucault with 'classical' transindividuality potentially extends and deepens each. This response concludes with examples of these problematic tensions as well as possibly fruitful combinations.